Pengaruh Pengembangan Sumber Daya Manusia, Mutasi Tempat Kerja Dan Motivasi Kerja Terhadap Kinerja Pegawai Aparatur Sipil Negara / ASN ( Studi pada RSUD R.T. NOTOPURO SIDOARJO) - Wildana, Muchamad Rizal; Djaelani, Abdul Kodir; Primanto, Alfian Budi (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study was conducted to determine and analyze the influence of human resource development, workplace transfer, and work motivation on the performance of civil servants / ASN RSUD R.T. Notopuro Sidoarjo. This type of research uses quantitative methods, with the data analysis technique used being multiple linear regression analysis. Sampling through probability sampling with the Slovin formula, the number of respondents was 85 people. The results show that human resource development, workplace transfer have a simultaneous effect on employee performance while work motivation does not have a simultaneous effect on employee performance, and each independent variable of human resource development, workplace transfer has a partial effect on employee performance, while work motivation has no partial effect on employee performance. Keywords: Human Resource Development, Workplace Transfer, Work Motivation, Employee Performance